Quality Environmental Practice Evaluation System (5SPAS) - Mohd Azlan, Nur Ayuni; Abu Bakar, Juhaida; Katuk, Norliza (Multidisciplinary Applied Research and Innovation, 2021)
The Quality Environmental Practice Evaluation System (5SPAS) is a system which can only be implemented in an organization with corrective and remedial action. According to the literature, private organizations’ systems are accessed solely on the perception of internal 5S practice. Meanwhile, the researchers in this study focused on the Institute of Quality Management, Universiti Utara Malaysia (IPQ UUM) internal and external 5S practices, as well as data gathered from auditors and IPQ staff. IPQ UUM had previously exclusively used the system manually. Thus, it is difficult to conduct an evaluation of quality environmental practice. As a result, there is a limit on how these actions can be carried out. Hence, this study created a web-based application for the IPQ UUM to conduct the evaluation. The aim of this work is to identify system requirements for the 5SPAS. Prototyping methodology has been adopted in the study. Firstly, the functional requirements were gathered through interviews. Three main functionalities have been identified: managing users, managing 5S practice evaluation criteria, and managing reports. Then, based on the requirements gathered, a prototype was created. Furthermore, the work must evaluate the usability of the 5SPAS using the Technology Acceptance Model (TAM) or any other appropriate metrics. Field testing was also conducted to assess the usability of the 5SPAS. Based on the field-testing results, it shows that overall, most of the respondents agree that 5SPAS is useful (83.34%), ease of use (81.65%), design (80%), and satisfaction (78.35%). The respondents also stated that 5SPAS is an awesome and good system. As a result of this work, users should be able to implement the 5SPAS effectively and efficiently. It can also serve as a future reference model for developers and researchers working on similar systems, such as developing a mobile application for 5SPAS.